Two-dimensional perovskites with alternating cations in the interlayer space for stable light-emitting diodes - Zhang Yiyue; Keshavarz Masoumeh; Debroye Elke; Fron Eduard; Rodríguez González Miriam Candelaria; Naumenko Denys; Amenitsch Heinz; Van de Vondel Joris; De Feyter Steven; Heremans Paul; Roeffaers Maarten B. J.; Qiu Weiming; et al. (Nanophotonics, 2021)
Lead halide perovskites have attracted tremendous attention in photovoltaics due to their impressive optoelectronic properties. However, the poor stability of perovskite-based devices remains a bottleneck for further commercial development. Two-dimensional perovskites have great potential in optoelectronic devices, as they are much more stable than their three-dimensional counterparts and rapidly catching up in performance. Herein, we demonstrate high-quality two-dimensional novel perovskite thin films with alternating cations in the interlayer space. This innovative perovskite provides highly stable semiconductor thin films for efficient near-infrared light-emitting diodes (LEDs). Highly efficient LEDs with tunable emission wavelengths from 680 to 770 nm along with excellent operational stability are demonstrated by varying the thickness of the interlayer spacer cation. Furthermore, the best-performing device exhibits an external quantum efficiency of 3.4% at a high current density (J) of 249 mA/cm2 and remains above 2.5% for a J up to 720 mA cm−2, leading to a high radiance of 77.5 W/Sr m2 when driven at 6 V. The same device also shows impressive operational stability, retaining almost 80% of its initial performance after operating at 20 mA/cm2 for 350 min. This work provides fundamental evidence that this novel alternating interlayer cation 2D perovskite can be a promising and stable photonic emitter.